Ancient genomes provide insights into family structure and the heredity of social status in the early Bronze Age of southeastern Europe - A. Žegarac (Nature Portfolio, 2021)
Abstract Twenty-four palaeogenomes from Mokrin, a major Early Bronze Age necropolis in southeastern Europe, were sequenced to analyse kinship between individuals and to better understand prehistoric social organization. 15 investigated individuals were involved in genetic relationships of varying degrees. The Mokrin sample resembles a genetically unstructured population, suggesting that the community’s social hierarchies were not accompanied by strict marriage barriers. We find evidence for female exogamy but no indications for strict patrilocality. Individual status differences at Mokrin, as indicated by grave goods, support the inference that females could inherit status, but could not transmit status to all their sons. We further show that sons had the possibility to acquire status during their lifetimes, but not necessarily to inherit it. Taken together, these findings suggest that Southeastern Europe in the Early Bronze Age had a significantly different family and social structure than Late Neolithic and Early Bronze Age societies of Central Europe.